Junior High School Students' Scientific Argumentation Skills on Conventional Biotechnology Materials - Friska, Reski Ivon; Siahaan, Parsaoran; Hendayana, Sumar (Journal of Educational Sciences, 2022)
Argumentation skills include important features for critical thinking that need to be trained to students. Being involved in argumentation leads students to be able to put forward arguments that are supported by data and scientific reasoning, argue with each other to consider the truth of alternative arguments so as to obtain an agreement that can be accounted for. The purpose of this study was to analyze students' scientific argumentation skills on biotechnology material using the Argument-Driven Inquiry (ADI) model. The method used in this study is a qualitative descriptive method. Students' scientific argumentation skills during the learning process were analyzed from transcripts of audio recordings and learning videos known as Transcript Based Lesson Analysis (TBLA). The results of this study indicate that learning with the Argument-Driven Inquiry (ADI) model can build students' scientific argumentation skills. The six categories of social negotiation have been identified from student conversations when involved in scientific arguments, but are still dominated by the idea construction components, namely information seeking and elaboration. Meanwhile, the components of criticism of ideas including challenging, supporting, rejecting and defending are not often used by students. This is due to the limited knowledge of students about the material and the low understanding of epistemic arguments where they are not accustomed to using scientific evidence to support their claims.